ANALISIS PENGARUH KECUKUPAN MODAL, LIKUIDITAS, KUALITAS AKTIVA, EFISIENSI OPERASIONAL, DAN RENTABILITAS TERHADAP PROFITABILITAS - Setiyadi Putra, Aditiya Ghanang; Merawati, Endang Etty; Parenrengi, Sudarmin (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to research the influence of Capital Adequacy Ratio (CAR), Loan to Deposits Ratio (LDR), Non Performing Loans (NPL), Operating Income Operating Expenses (BOPO), and Net Interest Margin (NIM) on Profitability (ROA). The type of research in this study is quantitative research. The population of this study is Commercial Bank listed in Indonesia Stock Exchange (IDX) that provides annual financial reports with the observation period between 2013-2017. There are 42 Populations. The sampling method used in this research is purposive sampling. There are 21 commercial banks that meet the criteria as the research samples. Data were analyzed using the method of Multiple Linear Regression. The results of this research indicate that partially CAR, NPL, and BOPO have a negative and significant effect on ROA, LDR has a positive but not significant effect on ROA and NIM has a positive and significant effect on ROA. Keywords: CAR, LDR, NPL, BOPO, NIM, ROA